Learning a non-native language in a naturalistic environment: Insights from behavioural and neuroimaging research - Vicky Chondrogianni (Frontiers Research Topics, 2015)
It is largely accepted in the relevant literature that successful learning of one or more non-native languages is affected by a number of factors that are independent of the target language(s) per se; these factors include the age of acquisition (AoA) of the target language(s), the type and amount of formal instruction the learners have received, as well as the amount of language use that the learners demonstrate. Recent experimental evidence suggests that one crucial factor for efficient native-like performance in the non-native language is the amount of naturalistic exposure, or immersion, that the learners receive to that language. This can be broadly defined as the degree to which language learners use their non-native language outside the classroom and for their day-to-day activities, and usually presupposes that the learners live in an environment where their non-native language is exclusively or mostly used. Existing literature has suggested that linguistic immersion can be beneficial for lexical and semantic acquisition in a non-native language, as well as for non-native morphological and syntactic processing. More recent evidence has also suggested that naturalistic learning of a non-native language can also have an impact on the patterns of brain activity underlying language processing, as well as on the structure of brain regions that are involved, expressed as changes in the grey matter structure. This Research Topic brings together studies on the effects of learning and speaking a non-native language in a naturalistic environment. These include more efficient or "native-like" processing in behavioural tasks tapping on language (lexicon, morphology, syntax), as well as changes in the brain structure and function, as revealed by neuroimaging studies.